Physicochemical changes in microplastics and formation of DBPs under ozonation. (June 2023) - Hao, Tianwei; Miao, Manhong; Wang, Tong; Xiao, Yihang; Yu, Bingqing; Zhang, Min; Ning, Xiaoyu; Li, Yao
Abstract: Microplastics (MPs) are substances that pose a risk to both human life and the environment. Their types and production are increasing year on year, and their potential to cause environmental pollution is a worldwide concern. Conventional water treatment processes, particularly coagulation and sedimentation, are not effective at removing all MPs. It is therefore important to assess the morphological changes in the MPs, i.e., the thermoplastic polyurethane (TPU) and polyethylene (PE), during ozonation and the dissolved organic carbon leaching as well as chloroform formation in the subsequent chlorination. The results show that the appearance and surface chemistry of the MPs changed during the ozonation process, most notably for TPU. The trichloromethane (CHCl3 ) generation during chlorination was 0.168 and 0.152 μmol/L for TPU and PE, respectively, and the ozone pretreatment significantly increased the CHCl3 yield of TPU, while it had a weak effect on PE. Additional disinfection byproducts (DBPs), including CHCl2 Br, CHClBr2, and CHBr3, were produced in the presence of bromide ions in the water column, and the total amount of DBPs produced by PE, PE-O, TPU, and TPU-O was significantly increased to 0.787, 0.814, 0.931, and 1.391 μmol/L, respectively. The study provides useful information for the environmental risk assessment of two representative MPs, i.e., TPU and MPs, in disinfection procedures for drinking water. Graphical abstract: Image 1 Highlights: Ozonation can change PE and TPU physicochemical properties. Pre-ozonation processes can increase O-functional groups on TPU surface. Pre-ozonation treatment can promote CHCl3 formation during TPU chlorination. Pre-ozonation can increase brominated DBPs formation.